Policy For Crime Murder Investigation By The Children In Polrestabes Semarang - Erwin Chan; Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
Issues that will be examined are: 1) How do criminal investigations policy murders committed by children in Polrestabes Semarang today? 2) How is the investigation of criminal policy of murder committed by children who should have been in the Indonesian National Police?This study uses empirical juridical approach method, the specifications in this research is descriptive. Data collection methods use primary data with interview techniques. The data analysis method used is the analysis of qualitative data.The study concluded that: 1) Policy murder investigation of criminal offenses committed by children in Polrestabes Semarang today in addressing the crime of child offenders who commit criminal acts be routed into diversion pursuant to Act No. 11 of 2012 on the Criminal Justice System Child. 2) Policies murder investigation of criminal offenses committed by children who should at the Indonesian National Police should be able to: a) Understand the scope of the duties and authority of the Police Child Protection. b) know the Juvenile Justice Act, Child Protection Act, the Child Welfare Act and the UN Convention on the Rights of the Child. c) Ability to interpret and discuss the procedure done in dealing with children in conflict with the law.Keywords: Policies; Investigation; Children Crime.